Concomitant Weekly Cisplatin and Radiotherapy for HPV‐Positive Oropharyngeal Squamous Cell Carcinoma in Japan. (23rd August 2013) - Mizumachi, Takatsugu; Homma, Akihiro; Sakashita, Tohohiro; Kano, Satoshi; Hatakeyama, Hiromitsu; Fukuda, Satoshi
Abstract : Objectives: The most common chemoradiotherapy regimen is high‐dose (100mg/m2) three‐weekly cisplatin with concomitant radiotherapy; however, this protocol is associated with acute and late toxicities. Recent study demonstrated that human papillomavirus (HPV)‐positive oropharyngeal squamous cell carcinoma (OPSCC) patients showed good prognosis. We reviewed the efficacy for concomitant weekly cisplatin and radiotherapy in patients with HPV‐positive OPSCC. Methods: Twenty‐two patients with untreated OPSCC were enrolled and evaluated at our institution from July 2006 to June 2012. Weekly cisplatin (40mg/m2) was given on weeks 1, 2, 3, 5, 6 and 7 with radiotherapy, which comprised a standard dose of 70 Gy delivered in 35 daily fractions over 7 weeks. The presence of HPV was analyzed using multiplex PCR method. Median follow‐up time was 26 months for surviving patients. Results: Of the 22 oropharyngeal carcinomas, 13 (59%) were HPV‐positive. Twenty‐one patients (95.4%) received the full dose of radiotherapy. Over the course of the chemotherapy, 14 patients (63.6%) received more than 200 mg/m2 cisplatin. The acute and late toxicity was manageable in all cases. HPV‐positive patients had better two‐year‐overall survival rates (90.0% vs 66.7%) than HPV‐negative patients. For patients who were HPV‐positive, 1 of 13 died of distant metastasis, but those who were HPV‐negative, 1 of 9 died of local recurrence and 2 of 9 died of distant metastasis. Conclusions: Because of its favorable outcome and less toxicity, concomitant weekly cisplatin and radiotherapy appears to be suitable treatment for HPV‐positive OPSCC.